On the Homogenization and Correctors of a Quasilinear Elliptic Problem in a Two-Component Domain with an Imperfect Interface - Borja, Genesis John G.; Roque, Marian P.; Cabarrubias, Bituin C. (Quezon City Institute of Mathematics, College of Science, University of the Philippines Diliman, 2015)
We study the homogenization of a quasilinear elliptic problem in a two-component domain, which has a unique solution. To this aim, we discuss and apply the periodic unfolding method in two-component domains to our problem, which has a jump of the solution on the periodic imperfect interface, proportional to the flux and dependent on a real parameter.
Thesis (Master of Science in Mathematics)--University of the Philippines Diliman
Bibliography: pages 48-49.
Keywords: Differential equations, partial; Thermal conductivity; Homogenization (Differential equations).; Matter -- Thermal properties